Urban and peri-urban plastic bag pollution: producers’ perceptions of the impacts of plastic bag ingestion by domestic ruminants in the commune of Dori in Burkina Faso - Akoudjin, Massouroudini; Ouédraogo, Aïcha; Boma, Soudah; Comboigo, Sidpakissidé Marius; Karambiri, Sheila Médina; Soha, Sesseya Arnaud Sas; Somda, Martin Bienvenu; Belem, Marie Gaston Adrien; Sawadogo, Rassablaga Dominique (International Journal of Environment, Agriculture and Biotechnology, 2023)
The phenomenon of pollution by plastic waste is a public health problem in Burkina Faso. The ingestion of these plastic bags by domestic ruminants causes enormous losses to producers. Thus, to have the involvement of these producers in the management of plastic, this study was initiated to collect their perceptions (knowledge, attitudes and practices) on this scourge of plastic ingestion by farm animals. It was conducted from May to June 2021 and involved 60 producers living in the urban and peri-urban area of the commune of Dori in Burkina Faso. The interviews focused on the characterization of their farms (breeding system, livestock diversity, animal feeding); their knowledge of the phenomenon of ingestion of plastic bags by domestic ruminants and its impact (mortality and loss of income) on farms; attitudes, practices in the face of the scourge and their proposed solutions. The survey revealed that animal feed was based essentially on natural grazing at 77% with supplementation for a minority of farms (6%) (p < 0.001). In addition, the extensive system based on transhumance was the most widespread because it concerned 83% (50) of the producers (p < 0.001). The ingestion of plastic bags by the animals is perceived by the producers as one of the main causes of the mortalities recorded in their farms, however the causes seem to be external to the farming systems, in view of the solutions they recommend. Respondents know the symptoms of plastic ingestion (weight loss (43%), persistent bloating (31%) often accompanied by a hardening of the abdomen and diarrhea (13%), anorexia (12 %) and a runny nose (1%)), but which can be confused with other parasitoses, and have traditional practices for diagnosing it. The study suggests that special arrangements be made for a better awareness of the management of plastic bags in the environment, with the support of environmental and public health technicians, municipal and communal authorities of Dori.